1998
DOI: 10.1093/ajcn/67.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistant starch on the colon in healthy volunteers: possible implications for cancer prevention

Abstract: Recent evidence suggests that resistant starch (RS) is the single most important substrate for bacterial carbohydrate fermentation in the human colon. During two 4-wk periods. 12 healthy volunteers consumed a controlled basal diet enriched with either amylomaize starch (55.2 +/- 3.5 g RS/d; high-RS diet) or available cornstarch (7.7 +/- 0.3 g RS/d; low-RS diet). Approximately 90% of the RS consumed disappeared during intestinal passage; increased fermentation was verified by elevated breath-hydrogen excretion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(130 citation statements)
references
References 37 publications
6
112
1
6
Order By: Relevance
“…However, the results of the present study indicate an increased moisture content of the faeces with increasing RRM intake, which suggests that RRM moderately moisturizes faecal matter and affects bulk as has been shown in other studies (Phillips et al, 1995;Cummings et al, 1996). The latter has been identified as potentially beneficial for colonic mucosal health and the prevention of large bowel intestinal disorders, notably by reducing pH, increasing luminal contents of short-chainfatty acids, reducing luminal ammonia, secondary bile acids and faecal water toxicity (Tomlin and Read, 1990;Cummings et al, 1992;Van Munster and Nagengast, 1993;Birkett et al, 1997;Hylla et al, 1998;Topping and Clifton, 2001). …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, the results of the present study indicate an increased moisture content of the faeces with increasing RRM intake, which suggests that RRM moderately moisturizes faecal matter and affects bulk as has been shown in other studies (Phillips et al, 1995;Cummings et al, 1996). The latter has been identified as potentially beneficial for colonic mucosal health and the prevention of large bowel intestinal disorders, notably by reducing pH, increasing luminal contents of short-chainfatty acids, reducing luminal ammonia, secondary bile acids and faecal water toxicity (Tomlin and Read, 1990;Cummings et al, 1992;Van Munster and Nagengast, 1993;Birkett et al, 1997;Hylla et al, 1998;Topping and Clifton, 2001). …”
Section: Discussionsupporting
confidence: 76%
“…RS is supposed to contribute to colonic health through effects on gut flora, intestinal pH reduction, secondary bile acids reduction, elevated butyrate production and reductions in putrefactive protein fermentation as well as in luminal ammonia concentrations. Although these effects are generally supposed to beneficially impact on health, not all studies show a positive outcome on measured clinical endpoints (Edwards et al, 1995;Hylla et al, 1998;Topping and Clifton, 2001). Type 4 RS may differ in fermentation behaviour depending on its modified molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship of satiety to postprandial glycaemic response is not clear (Barkeling et al, 1995), and the satiating effect seems to be a complex process involving multiple factors . Escaping digestion in the small intestine, resistant starch fraction present in HAWB become a substrate for colonic fermentation with possible implication in cancer (Hylla et al, 1998). Resistant starch was suspected to produce a relative high production of butyrate (Martin et al, 1998), considered as a bene®cial substrate against colonic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies have reported accurate RS measurements in diet and have carried out adequate faecal collections (Table 6), from which it can be seen that the average increase in stool weight is 1.5 g/g RS fed. A meta-analysis including data from six of these seven studies (Tomlin and Read, 1990;van Munster et al, 1994;Phillips et al, 1995;Cummings et al, 1996;Silvester et al, 1997;Heijnen et al, 1998;Hylla et al, 1998) (excluding Tomlin and Read, 1990; because no error measurements are given in the paper) has been carried out and the results are given in Figure 6. This shows a highly significant overall increase in mean daily stool weight for the group of 41.1 g/day (75.4 g s.e.m.…”
Section: Bowel Habitmentioning
confidence: 99%